Silicon carbide sintered body as well as preparation method and application thereof

By introducing rare earth silicate grain boundary phases into the silicon carbide sintered body, a stable grain boundary phase network is formed, which solves the problem of insufficient wear resistance of silicon carbide materials in deep-sea environments, and achieves high wear resistance of the material under seawater conditions.

CN119528581APending Publication Date: 2025-02-28LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411708820.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing silicon carbide materials cannot effectively meet the needs of friction and wear resistance in deep-sea environments, mainly due to the huge seawater pressure accelerates chemical reactions and mechanical wear.

Method used

By introducing rare earth silicate grain boundary phases into the silicon carbide sintered body, a grain boundary phase network of Yb2SiO5, Yb2Si2O7, Lu2SiO5 and Lu2Si2O7 phases is formed, and combined with the mechanical wear resistance of the silicon carbide crystal phase, the wear resistance of the material under seawater conditions is improved.

Benefits of technology

The high wear resistance of silicon carbide sintered bodies in seawater environments is achieved, which can not only suppress mechanical wear, but also reduce water corrosion wear, significantly improving the deep-sea application performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119528581A_ABST
    Figure CN119528581A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of ceramic materials, and particularly relates to a silicon carbide sintered body and a preparation method and application thereof. A grain boundary phase of the silicon carbide sintered body provided by the invention comprises a rare earth silicate grain boundary phase; the rare earth silicate grain boundary phase comprises one or more of Yb2SiO5, Yb2Si2O7, Lu2SiO5 and Lu2Si2O7, and the rare earth silicate grain boundary phase comprises one or more of Yb2SiO5, Yb2Si2O7, Lu2SiO5 and Lu2Si2O7. The silicon carbide sintered body provided by the invention comprises silicon carbide grains and a grain boundary phase, the grain boundary phase forms a rare earth silicate grain boundary phase network, and the main component of the grain boundary phase is one or more of Yb2SiO5, Yb2Si2O7, Lu2SiO5 and Lu2Si2O7. In the wear process of the silicon carbide sintered body provided by the invention, silicon carbide grains can inhibit mechanical wear, the existence of a grain boundary phase plays a role in reducing water corrosion wear, and finally, the wear resistance of the silicon carbide ceramic in a seawater environment is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramic materials, and specifically relates to a silicon carbide sintered body and a preparation method and application thereof. Background Art

[0002] Silicon carbide ceramics are widely used in high-performance dynamic sealing materials due to their high hardness, high strength, high modulus, high temperature resistance, and wear resistance. Under water lubrication conditions, silicon carbide is mainly corrosive and wear-resistant, which is mainly manifested as a chemical reaction between water and silicon carbide particles.

[0003] However, in deep-sea environments, on the one hand, dynamic seals require higher sealing pressure to maintain the sealing effect, resulting in very large contact loads and increased wear rates; on the other hand, the huge seawater pressure can accelerate chemical reactions, resulting in increased wear rates. This makes the current silicon carbide materials unable to meet the requirements of friction and wear resistance in deep-sea environments. Summary of the invention

[0004] The object of the present invention is to provide a silicon carbide sintered body and a preparation method and application thereof. The silicon carbide sintered body provided by the present invention has both mechanical wear resistance and seawater corrosion resistance. Therefore, the silicon carbide sintered body provided by the present invention has high wear resistance under seawater conditions.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] The present invention provides a silicon carbide sintered body, which comprises a silicon carbide crystalline phase and a grain boundary phase, wherein the grain boundary phase comprises a rare earth silicate grain boundary phase; the rare earth silicate grain boundary phase comprises one or more of Yb2SiO5, Yb2Si2O7, Lu2SiO5 and Lu2Si2O7.

[0007] Preferably, the total content of the Yb2SiO5, Yb2Si2O7, Lu2SiO5 and Lu2Si2O7 phases accounts for more than 70wt% of the total amount of the grain boundary phase.

[0008] Preferably, the content of the silicon carbide crystalline phase accounts for 88-94 wt % of the silicon carbide sintered body, and the content of the grain boundary phase accounts for 6-12 wt % of the silicon carbide sintered body.

[0009] The present invention provides a method for preparing the silicon carbide sintered body described in the above technical solution, comprising the following steps:

[0010] Mixing silicon carbide powder and sintering aid powder to obtain a mixed powder, wherein the sintering aid includes at least one of rare earth oxides, rare earth silicates and silicon oxide, and the ratio of the total molar amount of the rare earth oxide converted in the mixed powder to the total molar amount of silicon dioxide converted in the mixed powder is 1:0.8-1.3 or 1:1.8-2.1;

[0011] The mixed powder is sintered to obtain the silicon carbide sintered body.

[0012] Preferably, the total mass of the rare earth oxides and silicon dioxide in the mixed powder accounts for 6-12 wt % of the mass of the mixed powder.

[0013] Preferably, the particle sizes of the silicon carbide powder and the sintering aid powder are independently 0.05 to 200 microns.

[0014] Preferably, the mixing comprises the following steps:

[0015] Silicon carbide powder, sintering aid powder, grinding balls and solvent are mixed and ground to obtain slurry, wherein the grinding includes one or more of planetary ball milling, drum ball milling and sand milling, the solvent includes ethanol and / or water, and the grinding time is 2 to 24 hours;

[0016] The slurry is dried and sieved in sequence to obtain the mixed powder.

[0017] Preferably, the sintering includes pressureless sintering, hot pressing sintering or spark plasma sintering after dry pressing;

[0018] The sintering temperature is 1700-2100° C., and the heat preservation time is 5-120 minutes.

[0019] The present invention provides the use of the silicon carbide sintered body described in the above technical solution or the silicon carbide sintered body prepared by the preparation method described in the above technical solution in sealing materials.

[0020] Preferably, the sealing material is a dynamic sealing material used in deep sea conditions, and the seawater depth in the deep sea conditions is ≥ 1000 meters.

[0021] The present invention provides a silicon carbide sintered body, the silicon carbide sintered body comprises a silicon carbide crystalline phase and a grain boundary phase, the grain boundary phase comprises a rare earth silicate grain boundary phase; the rare earth silicate grain boundary phase comprises one or more of Yb2SiO5, Yb2Si2O7, Lu2SiO5 and Lu2Si2O7. The silicon carbide sintered body provided by the present invention comprises a silicon carbide crystalline phase (i.e., silicon carbide grains) and a grain boundary phase, the grain boundary phase forms a rare earth silicate grain boundary phase network, and the main components of the grain boundary phase are one or more of Yb2SiO5 phase, Yb2Si2O7 phase, Lu2SiO5 phase and Lu2Si2O7 phase. Compared with other rare earth silicate phases, rare earth oxide phases and silicon oxide phases, Yb2SiO5 phase, Yb2Si2O7 phase, Lu2SiO5 phase or Lu2Si2O7 phase has obvious water corrosion resistance. During the wear process of the silicon carbide sintered body provided by the present invention, the silicon carbide grains can inhibit the progress of mechanical wear, and the presence of the grain boundary phases Yb2SiO5, Yb2Si2O7, Lu2SiO5 or Lu2Si2O7 plays a role in reducing water corrosion wear, ultimately greatly improving the wear resistance of silicon carbide ceramics in seawater environments.

[0022] The present invention provides a method for preparing a silicon carbide sintered body according to the above technical solution, comprising the following steps: mixing silicon carbide powder and sintering aid powder to obtain a mixed powder, wherein the sintering aid comprises at least one of rare earth oxide, rare earth silicate and silicon oxide, and the ratio of the total molar amount of rare earth oxide converted in the mixed powder to the total molar amount of silicon dioxide converted in the mixed powder is 1:0.8-1.3 or 1:1.8-2.1; sintering the mixed powder to obtain the silicon carbide sintered body. The present invention controls the dosage ratio of the raw materials in the mixed powder, wherein the total molar ratio of rare earth oxide and silicon dioxide contained in the mixed powder is close to 1:1 (i.e. 1:0.8-1.3) or 1:2 (i.e. 1:1.8-2.1), and in the sintered body obtained by sintering, the grain boundary phase is more likely to form phases such as Yb2SiO5, Yb2Si2O7, Lu2SiO5, and Lu2Si2O7. These four phases are more resistant to seawater corrosion than silicon carbide phase, silicon oxide phase, rare earth oxide phase and other rare earth silicate phases. Therefore, the silicon carbide grains in the silicon carbide sintered body obtained by the preparation method provided by the present invention have mechanical wear resistance, and the grain boundary phase has seawater corrosion resistance, so the prepared sintered body has high wear resistance under seawater conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a three-dimensional picture of the wear scar of the sample prepared in Example 1 after being worn for 2 hours in a sea depth of 1000 meters. DETAILED DESCRIPTION

[0024] The present invention provides a silicon carbide sintered body, which comprises a silicon carbide crystalline phase and a grain boundary phase, wherein the grain boundary phase comprises a rare earth silicate grain boundary phase; the rare earth silicate grain boundary phase comprises one or more of Yb2SiO5, Yb2Si2O7, Lu2SiO5 and Lu2Si2O7.

[0025] In the present invention, unless otherwise specified, all preparation raw materials / components are commercially available products well known to those skilled in the art.

[0026] The silicon carbide sintered body provided by the present invention comprises a silicon carbide crystalline phase, namely silicon carbide grains. The silicon carbide grains in the silicon carbide sintered body have the characteristic of being resistant to mechanical wear. In the present invention, the content of the silicon carbide crystalline phase preferably accounts for 88 to 94 wt% of the silicon carbide sintered body.

[0027] The silicon carbide sintered body provided by the present invention comprises a grain boundary phase, wherein the crystalline phase is located at the grain boundary of the silicon carbide grains, and wherein the crystalline phase forms a grain boundary phase network at the grain boundary of the silicon carbide grains. In the present invention, the grain boundary phase comprises a rare earth silicate grain boundary phase; the rare earth silicate grain boundary phase comprises one or more of Yb2SiO5, Yb2Si2O7, Lu2SiO5 and Lu2Si2O7. In the present invention, the total content of the Yb2SiO5, Yb2Si2O7, Lu2SiO5 and Lu2Si2O7 preferably accounts for more than 70wt% of the total amount of the grain boundary phase. The content of the grain boundary phase preferably accounts for 6-12wt% of the silicon carbide sintered body.

[0028] In the present invention, the main component of the grain boundary phase is one or more of Yb2SiO5, Yb2Si2O7, Lu2SiO5, and Lu2Si2O7. During the wear process, the silicon carbide grains can inhibit the progress of mechanical wear. The presence of the grain boundary phase plays a role in reducing water corrosion and wear, and ultimately greatly improves the wear resistance of the silicon carbide sintered body in the seawater environment.

[0029] The present invention provides a method for preparing the silicon carbide sintered body described in the above technical solution, comprising the following steps:

[0030] Mixing silicon carbide powder and sintering aid powder to obtain a mixed powder, wherein the sintering aid includes at least one of rare earth oxides, rare earth silicates and silicon oxide, and the ratio of the total molar amount of the rare earth oxide converted in the mixed powder to the total molar amount of silicon dioxide converted in the mixed powder is 1:0.8-1.3 or 1:1.8-2.1;

[0031] The mixed powder is sintered to obtain the silicon carbide sintered body.

[0032] The present invention mixes silicon carbide powder and sintering aid powder to obtain a mixed powder, wherein the sintering aid includes at least one of rare earth oxides, rare earth silicates and silicon oxide, and the ratio of the total molar amount of rare earth oxides converted in the mixed powder to the total molar amount of silicon dioxide converted in the mixed powder is 1:0.8-1.3 or 1:1.8-2.1.

[0033] In the present invention, the particle size of the silicon carbide powder is preferably 0.05 to 200 microns, and in the embodiments it is specifically 1 micron, 10 microns, 0.05 microns or 200 microns. In the present invention, the present invention needs to consider the content of silicon dioxide introduced into the surface oxide layer of the silicon carbide particles. The present invention calculates the mass of silicon dioxide contained in the silicon carbide powder based on the oxygen content of the silicon carbide powder. In the specific implementation of the present invention, the oxygen content of the silicon carbide powder is specifically 0.5wt%, 0.3wt%, 0.9wt% or 0.8wt%.

[0034] In the present invention, the particle size of the sintering aid powder is preferably 0.05 to 200 microns, and in the embodiments, it is specifically 0.1 microns, 1 micron, 0.5 microns, 50 microns, 0.05 microns or 100 microns. The rare earth oxide includes ytterbium oxide (Yb2O3) powder and / or lutetium oxide (Lu2O3) powder. The rare earth silicate includes ytterbium silicate powder and / or lutetium silicate powder. The ytterbium silicate powder preferably includes Yb2SiO5 and / or Yb2Si2O7. The lutetium silicate powder preferably includes Lu2SiO5 and / or Lu2Si2O7. In a specific embodiment of the present invention, the sintering aid powder preferably includes at least two of rare earth oxides, rare earth silicates and silicon oxide, and specifically includes lutetium oxide powder and Lu2Si2O7 powder, ytterbium oxide powder and Yb2SiO5 powder, ytterbium oxide powder and Yb2Si2O7 powder, lutetium oxide powder and Lu2SiO5 powder, silicon oxide powder, ytterbium oxide powder and lutetium oxide powder, silicon oxide powder and lutetium oxide powder, or silicon oxide powder and ytterbium oxide powder. The total molar amount of rare earth oxides converted in the mixed powder is the sum of the molar amount of rare earth oxides in the mixed powder and the molar amount of rare earth oxides converted from rare earth silicates. The present invention regards the rare earth silicate as a combination of rare earth oxides and silicon dioxide, such as 1 mol Yb2SiO5 is equivalent to 1 mol Yb2O3 and 1 mol SiO2, and 1 mol Lu2Si2O7 is equivalent to 1 mol Lu2O3 and 2 mol SiO2. The total molar amount of silicon dioxide converted in the mixed powder is the sum of the molar amount of silicon oxide in the sintering aid and the molar amount of silicon oxide calculated from the oxygen content of the silicon carbide powder. In the present invention, the ratio of the total molar amount of rare earth oxides converted in the mixed powder to the total molar amount of silicon dioxide converted in the mixed powder is 1:0.8-1.3 or 1:1.8-2.1, preferably 1:0.9-1.2, and specifically 1:1, 1:0.8, 1:1.3, 1:1.8, 1:2 or 1:2.1 in the embodiments. In the present invention, the raw materials are designed so that the total molar ratio of rare earth oxides and silicon dioxide is closer to 1:1 or 1:2, and the grain boundary phase in the sintered body is more likely to form phases such as Yb2SiO5, Yb2Si2O7, Lu2SiO5, and Lu2Si2O7, and the content of the Yb2SiO5, Yb2Si2O7, Lu2SiO5, and Lu2Si2O7 phases in the obtained silicon carbide sintered body preferably accounts for more than 70wt% of the total amount of the grain boundary phase. This phase is more resistant to seawater corrosion than silicon carbide phase, silicon oxide phase, rare earth oxide phase, and other rare earth silicate phases. In the sintered body, silicon carbide grains have mechanical wear resistance, while the grain boundary phase has seawater corrosion resistance, so the prepared sintered body has high wear resistance under seawater conditions.

[0035] In the present invention, the total mass of rare earth oxides and silicon dioxide converted in the mixed powder is the sum of the mass of rare earth oxides in the sintering aid, the mass of rare earth oxides converted from rare earth silicates in the sintering aid, the mass of silicon oxide converted from rare earth silicates in the sintering aid, and the mass of silicon oxide in the sintering aid. The total mass of rare earth oxides and silicon dioxide converted in the mixed powder preferably accounts for 6-12wt% of the mass of the mixed powder, more preferably 8-11wt%, and specifically 10wt%, 12wt%, 8wt%, 7wt% or 6wt% in the embodiment. The present invention preferably controls the total mass of rare earth oxides and silicon dioxide converted in the mixed powder to preferably account for 6-12wt% of the mass of the mixed powder, so that the content of grain boundary phase in the obtained silicon carbide sintered body preferably accounts for 6-12wt% of the silicon carbide sintered body, thereby ensuring that the silicon carbide sintered body has a high degree of densification and is resistant to mechanical wear.

[0036] In the present invention, the mixing preferably comprises the following steps:

[0037] Silicon carbide powder, sintering aid powder, grinding balls and solvent are mixed and ground to obtain slurry, wherein the grinding includes one or more of planetary ball milling, drum ball milling and sand milling, the solvent includes ethanol and / or water, and the grinding time is 2 to 24 hours;

[0038] The slurry is dried and sieved in sequence to obtain the mixed powder.

[0039] The present invention mixes silicon carbide powder, sintering aid powder, grinding balls and solvent for grinding to obtain a slurry. In the present invention, the grinding balls preferably include one or more of silicon carbide balls, silicon nitride balls and agate balls, and more preferably include silicon carbide balls or agate balls. The solvent preferably includes ethanol and / or water. The grinding preferably includes one or more of planetary ball milling, drum ball milling and sand milling, and more preferably planetary ball milling. The present invention has no special requirements for the amount of grinding balls and solvents used in the grinding, as long as the grinding is carried out smoothly. In the present invention, the grinding time is preferably 2 to 24 hours.

[0040] After obtaining the slurry, the present invention sequentially dries and sieves the slurry to obtain the mixed powder. In the present invention, the specific implementation of the drying is preferably spray drying or drying, and the drying is preferably carried out in a blast drying oven, the drying temperature is preferably 50 to 60° C., and the drying time is preferably 3 to 12 hours. The present invention preferably removes the grinding balls used for the grinding by the screening.

[0041] After obtaining the mixed powder, the present invention sintered the mixed powder to obtain the silicon carbide sintered body. In the present invention, the sintering preferably includes pressureless sintering, hot pressing sintering or spark plasma sintering after dry pressing. The pressureless sintering after dry pressing preferably includes dry pressing, cold isostatic pressing and pressureless sintering in sequence. The pressure of the dry pressing is preferably 30 to 40 MPa. The pressure of the cold isostatic pressing is preferably 150 to 200 MPa. The pressureless sintering is carried out in a protective gas atmosphere, and the protective gas is preferably an inert gas, specifically argon in the embodiment. The pressure of the hot pressing is preferably 40 to 50 MPa. The pressure of the spark plasma sintering is preferably 40 to 50 MPa. In the present invention, the sintering temperature is 1700 to 2100°C, specifically 1900°C, 1800°C, 1700°C, 2100°C in the embodiment; the holding time is 5 to 120 minutes, specifically 2 hours, 0.5 hours, 5 minutes or 1 hour in the embodiment.

[0042] The present invention provides the use of the silicon carbide sintered body described in the above technical solution or the silicon carbide sintered body prepared by the preparation method described in the above technical solution in sealing materials.

[0043] In the present invention, the sealing material is specifically a dynamic sealing material used under deep sea conditions, the seawater depth under the deep sea conditions is ≥1000 meters; the pressure under the deep sea conditions is ≥10MPa.

[0044] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0045] Example 1

[0046] Weigh 90.85g of silicon carbide powder with an average particle size of 1 micron and an oxygen content of 0.5wt%, 0.47g of silicon oxide powder with an average particle size of 0.5 micron, and 8.68g of ytterbium oxide powder with an average particle size of 1 micron and place them in a ball mill. At this time, it can be calculated that the silicon carbide powder raw material contains about 0.85g of silicon dioxide, the total amount of silicon dioxide is 1.32g, the molar ratio of ytterbium oxide to silicon oxide is about 1:1, and the total amount of ytterbium oxide and silicon oxide accounts for 10wt% of the total amount of raw materials. Add 100g of silicon carbide balls and 60g of ethanol to planetary ball mill for 4 hours, dry the slurry after ball milling in a blast drying oven at 50℃ for 3 hours, and obtain the sample after sieving. The powder was dry pressed at 40 MPa, cold isostatically pressed at 150 MPa, and pressurelessly sintered at 1900°C for 2 hours in an argon atmosphere to obtain a silicon carbide sintered body. The sintered body was polished and subjected to in-situ friction and wear tests in 10 MPa seawater conditions to simulate a 1000-meter sea depth environment. The wear volume was tested using white light interferometry to calculate the wear rate. Figure 1This is a three-dimensional picture of the wear scar of the sample prepared in Example 1 after being worn for 2 hours in a sea depth of 1000 meters.

[0047] Example 2

[0048] Weigh 88.45g of silicon carbide powder with an average particle size of 1 micron and an oxygen content of 0.3wt%, 0.81g of silicon oxide powder with an average particle size of 0.5 micron, and 10.70g of ytterbium oxide powder with an average particle size of 1 micron and place them in a ball mill. At this time, it can be calculated that the silicon carbide powder raw material contains about 0.50g of silicon dioxide, the total amount of silicon dioxide is 1.31g, the molar ratio of ytterbium oxide to silicon oxide is about 1:0.8, and the total amount of ytterbium oxide and silicon oxide accounts for 12wt% of the total amount of raw materials. Add 100g of silicon nitride balls and 60g of ethanol to planetary ball mill for 4 hours, dry the slurry after ball milling in a blast drying oven at 50℃ for 3 hours, and obtain the sample after sieving. The powder was dry pressed at 40 MPa, cold isostatically pressed at 150 MPa, and pressurelessly sintered at 1900°C for 2 hours in an argon atmosphere to obtain a silicon carbide sintered body. The sintered body was polished and subjected to in-situ friction and wear tests in 10 MPa seawater conditions to simulate a 1000-meter sea depth environment. The wear volume was tested using white light interferometry to calculate the wear rate.

[0049] Example 3

[0050] Weigh 91.55g of silicon carbide powder with an average particle size of 1 micron and an oxygen content of 0.9wt%, 0.11g of silicon oxide powder with an average particle size of 0.5 micron, and 8.35g of ytterbium oxide powder with an average particle size of 1 micron and place them in a ball mill. At this time, it can be calculated that the silicon carbide powder raw material contains about 1.55g of silicon dioxide, the total amount of silicon dioxide is 1.66g, the molar ratio of ytterbium oxide to silicon oxide is about 1:1.3, and the total amount of ytterbium oxide and silicon oxide accounts for 10wt% of the total amount of raw materials. Add 100g of agate balls and 60g of ethanol to planetary ball mill for 4 hours, dry the slurry after ball milling in a blast drying oven at 50℃ for 3 hours, and obtain the sample after sieving. The powder was dry pressed at 40MPa, cold isostatic pressed at 150MPa, and pressureless sintered at 1900℃ for 2 hours in an argon atmosphere to obtain a silicon carbide sintered body. After polishing, the sintered body was subjected to in-situ friction and wear tests in 10MPa seawater conditions to simulate a 1000-meter sea depth environment. The wear volume was tested using a white light interferometer to calculate the wear rate.

[0051] Example 4

[0052] Weigh 93.58g of silicon carbide powder with an average particle size of 10 microns and an oxygen content of 0.9wt%, 0.14g of silicon oxide powder with an average particle size of 0.5 microns, and 6.28g of ytterbium oxide powder with an average particle size of 1 micron and place them in a ball mill. At this time, it can be calculated that the silicon carbide powder raw material contains about 1.58g of silicon dioxide, the total amount of silicon dioxide is 1.72g, the molar ratio of ytterbium oxide to silicon oxide is about 1:1.8, and the total amount of ytterbium oxide and silicon oxide accounts for 8wt% of the total amount of raw materials. Add 100g of silicon carbide balls and 60g of deionized water to perform roller ball milling for 24 hours. The slurry after ball milling is dried in a blast drying oven at 50℃ for 3 hours, and the sample is obtained after sieving. The powder was dry pressed at 40 MPa, cold isostatically pressed at 150 MPa, and pressurelessly sintered at 1900°C for 2 hours in an argon atmosphere to obtain a silicon carbide sintered body. The sintered body was polished and subjected to in-situ friction and wear tests in 10 MPa seawater conditions to simulate a 1000-meter sea depth environment. The wear volume was tested using white light interferometry to calculate the wear rate.

[0053] Example 5

[0054] Weigh 94.42g of silicon carbide powder with an average particle size of 0.05 microns and an oxygen content of 0.8wt%, 0.22g of silicon oxide powder with an average particle size of 0.5 microns, and 5.36g of ytterbium oxide powder with an average particle size of 1 micron and place them in a ball mill. At this time, it can be calculated that the silicon carbide powder raw material contains about 1.42g of silicon dioxide, the total amount of silicon dioxide is 1.64g, the molar ratio of ytterbium oxide to silicon oxide is about 1:2, and the total amount of ytterbium oxide and silicon oxide accounts for 7wt% of the total amount of raw materials. Add 100g of silicon carbide balls and 60g of ethanol to planetary ball mill for 4 hours, dry the slurry after ball milling in a blast drying oven at 50℃ for 3 hours, and obtain the sample after sieving. The powder was dry pressed at 40 MPa, cold isostatically pressed at 150 MPa, and pressurelessly sintered at 1900°C for 2 hours in an argon atmosphere to obtain a silicon carbide sintered body. The sintered body was polished and subjected to in-situ friction and wear tests in 10 MPa seawater conditions to simulate a 1000-meter sea depth environment. The wear volume was tested using white light interferometry to calculate the wear rate.

[0055] Example 6

[0056] Weigh 94.53g of silicon carbide powder with an average particle size of 0.05 microns and an oxygen content of 0.3wt%, 0.92g of silicon oxide powder with an average particle size of 0.1 microns, and 4.54g of ytterbium oxide powder with an average particle size of 0.1 microns and place them in a ball mill. At this time, it can be calculated that the silicon carbide powder raw material contains about 0.53g of silicon dioxide, the total amount of silicon dioxide is 1.45g, the molar ratio of ytterbium oxide to silicon oxide is about 1:2.1, and the total amount of ytterbium oxide and silicon oxide accounts for 6wt% of the total raw material. Add 100g of silicon carbide balls and 60g of ethanol to planetary ball mill for 2 hours, dry the slurry after ball milling in a blast drying oven at 50℃ for 3 hours, and obtain the sample after sieving. The powder was hot pressed at 40MPa and sintered at 1800℃ for 0.5 hours to obtain a silicon carbide sintered body. After polishing, the sintered body was subjected to in-situ friction and wear test in 10MPa seawater conditions to simulate a 1000-meter sea depth environment. The wear volume was tested using white light interferometry to calculate the wear rate.

[0057] Example 7

[0058] Weigh 90.85g of silicon carbide powder with an average particle size of 1 micron and an oxygen content of 0.5wt%, 0.46g of silicon oxide powder with an average particle size of 0.5 micron, and 8.69g of lutetium oxide powder with an average particle size of 1 micron and place them in a ball mill. At this time, it can be calculated that the silicon carbide powder raw material contains about 0.85g of silicon dioxide, the total amount of silicon dioxide is 1.31g, the molar ratio of lutetium oxide to silicon oxide is about 1:1, and the total amount of lutetium oxide and silicon oxide accounts for 10wt% of the total amount of raw materials. Add 100g of silicon carbide balls and 60g of ethanol to planetary ball mill for 8 hours, dry the slurry after ball milling in a blast drying oven at 50℃ for 3 hours, and obtain the sample after sieving. The powder was sintered at 40MPa and 1700℃ for 5 minutes using discharge plasma to obtain a silicon carbide sintered body. After polishing, the sintered body was subjected to in-situ friction and wear testing in 10MPa seawater conditions to simulate a 1000-meter sea depth environment. The wear volume was tested using white light interferometry to calculate the wear rate.

[0059] Example 8

[0060] Weigh 90.85g of silicon carbide powder with an average particle size of 200 microns and an oxygen content of 0.5wt%, 0.46g of silicon oxide powder with an average particle size of 100 microns, 2g of ytterbium oxide powder with an average particle size of 50 microns, and 6.69g of lutetium oxide powder with an average particle size of 50 microns and place them in a ball mill. At this time, it can be calculated that the silicon carbide powder raw material contains about 0.85g of silicon dioxide, the total amount of silicon dioxide is 1.31g, the molar ratio of the sum of lutetium oxide and ytterbium oxide to silicon oxide is about 1:1, and the total amount of ytterbium oxide, lutetium oxide and silicon oxide accounts for 10wt% of the total amount of raw materials. Add 100g of silicon carbide balls and 60g of ethanol to planetary ball mill for 24 hours, dry the slurry after ball milling in a blast drying oven at 50℃ for 3 hours, and obtain the sample after sieving. The powder was dry pressed at 40 MPa, cold isostatically pressed at 150 MPa, and pressurelessly sintered at 2100°C for 30 minutes in an argon atmosphere to obtain a silicon carbide sintered body. The sintered body was polished and subjected to in-situ friction and wear tests in 10 MPa seawater conditions to simulate a 1000-meter sea depth environment. The wear volume was tested using white light interferometry to calculate the wear rate.

[0061] Example 9

[0062] Weigh 90.85g of silicon carbide powder with an average particle size of 1 micron and an oxygen content of 0.5wt%, 5.64g of lutetium oxide powder with an average particle size of 0.5 micron, and 3.05g of Lu2SiO5 powder with an average particle size of 1 micron and place them in a ball mill. At this time, it can be calculated that the silicon carbide powder raw material contains about 0.85g of silicon dioxide, the total amount of silicon dioxide is 1.31g, the molar ratio of lutetium oxide (including lutetium oxide powder and lutetium oxide converted from Lu2SiO5 powder) to silicon oxide is about 1:1, and the total amount of lutetium oxide (including lutetium oxide powder and lutetium oxide converted from Lu2SiO5 powder) and silicon oxide accounts for 10wt% of the total amount of raw materials. Add 100g of silicon carbide balls and 60g of ethanol to planetary ball mill for 4 hours, dry the slurry after ball milling in a blast drying oven at 50℃ for 3 hours, and obtain the sample after sieving. The powder was dry pressed at 40 MPa, cold isostatically pressed at 150 MPa, and pressurelessly sintered at 1900°C for 2 hours in an argon atmosphere to obtain a silicon carbide sintered body. The sintered body was polished and subjected to in-situ friction and wear tests in 10 MPa seawater conditions to simulate a 1000-meter sea depth environment. The wear volume was tested using white light interferometry to calculate the wear rate.

[0063] Example 10

[0064] Weigh 94.53g of silicon carbide powder with an average particle size of 1 micron and an oxygen content of 0.5wt%, 1.52g of ytterbium oxide powder with an average particle size of 0.5 micron, and 3.02g of Yb2Si2O7 powder with an average particle size of 1 micron and place them in a ball mill. At this time, it can be calculated that the silicon carbide powder raw material contains about 0.53g of silicon dioxide, the total amount of silicon dioxide (silicon dioxide converted from silicon dioxide and Yb2Si2O7 powder in the silicon carbide powder raw material) is 1.45g, the molar ratio of ytterbium oxide (including ytterbium oxide powder and ytterbium oxide converted from Yb2Si2O7 powder) to silicon oxide is about 1:2.1, and the total amount of ytterbium oxide and silicon oxide accounts for 6wt% of the total amount of raw materials. Add 100g of silicon carbide balls and 60g of ethanol to planetary ball mill for 4 hours, dry the slurry after ball milling in a blast drying oven at 50℃ for 3 hours, and obtain the sample after sieving. The powder was dry pressed at 40 MPa, cold isostatically pressed at 150 MPa, and pressurelessly sintered at 1900°C for 2 hours in an argon atmosphere to obtain a silicon carbide sintered body. The sintered body was polished and subjected to in-situ friction and wear tests in 10 MPa seawater conditions to simulate a 1000-meter sea depth environment. The wear volume was tested using white light interferometry to calculate the wear rate.

[0065] Embodiment 11

[0066] Weigh 90.85g of silicon carbide powder with an average particle size of 1 micron and an oxygen content of 0.5wt%, 5.64g of ytterbium oxide powder with an average particle size of 0.5 micron, and 3.05g of Yb2SiO5 powder with an average particle size of 1 micron and place them in a ball mill. At this time, it can be calculated that the silicon carbide powder raw material contains about 0.85g of silicon dioxide, the total amount of silicon dioxide is 1.31g, the molar ratio of ytterbium oxide to silicon oxide is about 1:1, and the total amount of ytterbium oxide and silicon oxide accounts for 10wt% of the total amount of raw materials. Add 100g of silicon carbide balls and 60g of ethanol to planetary ball mill for 4 hours, dry the slurry after ball milling in a blast drying oven at 50℃ for 3 hours, and obtain the sample after sieving. The powder was dry pressed at 40 MPa, cold isostatically pressed at 150 MPa, and pressurelessly sintered at 1900°C for 1 hour in an argon atmosphere to obtain a silicon carbide sintered body. The sintered body was polished and subjected to in-situ friction and wear tests in 10 MPa seawater conditions to simulate a 1000-meter sea depth environment. The wear volume was tested using white light interferometry to calculate the wear rate.

[0067] Example 12

[0068] Weigh 94.53g of silicon carbide powder with an average particle size of 1 micron and an oxygen content of 0.5wt%, 1.52g of lutetium oxide powder with an average particle size of 0.5 micron, and 3.02g of Lu2Si2O7 powder with an average particle size of 1 micron and place them in a ball mill. At this time, it can be calculated that the silicon carbide powder raw material contains about 0.53g of silicon dioxide, the total amount of silicon dioxide is 1.45g, the molar ratio of lutetium oxide to silicon oxide is about 1:2.1, and the total amount of lutetium oxide and silicon oxide accounts for 6wt% of the total amount of raw materials. Add 100g of silicon carbide balls and 60g of ethanol to planetary ball mill for 4 hours, dry the slurry after ball milling in a blast drying oven at 50℃ for 3 hours, and obtain the sample after sieving. The powder was dry pressed at 40 MPa, cold isostatically pressed at 150 MPa, and pressurelessly sintered at 1900°C for 1 hour in an argon atmosphere to obtain a silicon carbide sintered body. The sintered body was polished and subjected to in-situ friction and wear tests in 10 MPa seawater conditions to simulate a 1000-meter sea depth environment. The wear volume was tested using white light interferometry to calculate the wear rate.

[0069] Comparative Example 1

[0070] Weigh 90.85g of silicon carbide powder with an average particle size of 1 micron and an oxygen content of 0.5wt%, 0.11g of silicon oxide powder with an average particle size of 0.5 micron, and 9.04g of ytterbium oxide powder with an average particle size of 1 micron and place them in a ball mill. At this time, it can be calculated that the silicon carbide powder raw material contains about 0.85g of silicon dioxide, the total amount of silicon dioxide is 0.96g, the molar ratio of ytterbium oxide to silicon oxide is about 1:0.7, and the total amount of ytterbium oxide and silicon oxide accounts for 10wt% of the total amount of raw materials. Add 100g of silicon carbide balls and 60g of ethanol to planetary ball mill for 4 hours, dry the slurry after ball milling in a blast drying oven at 50℃ for 3 hours, and obtain the sample after sieving. The powder was dry pressed at 40 MPa, cold isostatically pressed at 150 MPa, and pressurelessly sintered at 1900°C for 2 hours in an argon atmosphere to obtain a silicon carbide sintered body. The sintered body was polished and subjected to in-situ friction and wear tests in 10 MPa seawater conditions to simulate a 1000-meter sea depth environment. The wear volume was tested using white light interferometry to calculate the wear rate.

[0071] Comparative Example 2

[0072] Weigh 90.85g of silicon carbide powder with an average particle size of 1 micron and an oxygen content of 0.5wt%, 1.01g of silicon oxide powder with an average particle size of 0.5 micron, and 8.13g of ytterbium oxide powder with an average particle size of 1 micron and place them in a ball mill. At this time, it can be calculated that the silicon carbide powder raw material contains about 0.85g of silicon dioxide, the total amount of silicon dioxide is 1.86g, the molar ratio of ytterbium oxide to silicon oxide is about 1:1.5, and the total amount of ytterbium oxide and silicon oxide accounts for 10wt% of the total amount of raw materials. Add 100g of silicon carbide balls and 60g of ethanol to planetary ball mill for 4 hours, dry the slurry after ball milling in a blast drying oven at 50℃ for 3 hours, and obtain the sample after sieving. The powder was dry pressed at 40 MPa, cold isostatically pressed at 150 MPa, and pressurelessly sintered at 1900°C for 2 hours in an argon atmosphere to obtain a silicon carbide sintered body. The sintered body was polished and subjected to in-situ friction and wear tests in 10 MPa seawater conditions to simulate a 1000-meter sea depth environment. The wear volume was tested using white light interferometry to calculate the wear rate.

[0073] Comparative Example 3

[0074] Weigh 96.91g of silicon carbide powder with an average particle size of 1 micron and an oxygen content of 0.5wt%, 0.02g of silicon oxide powder with an average particle size of 0.5 micron, and 3.07g of ytterbium oxide powder with an average particle size of 1 micron and place them in a ball mill. At this time, it can be calculated that the silicon carbide powder raw material contains about 0.91g of silicon dioxide, the total amount of silicon dioxide is 0.93g, the molar ratio of ytterbium oxide to silicon oxide is about 1:2, and the total amount of ytterbium oxide and silicon oxide accounts for 4wt% of the total raw material. Add 100g of silicon carbide balls and 60g of ethanol to planetary ball mill for 4 hours, dry the slurry after ball milling in a blast drying oven at 50℃ for 3 hours, and obtain the sample after sieving. The powder was dry pressed at 40 MPa, cold isostatically pressed at 150 MPa, and pressurelessly sintered at 1900°C for 2 hours in an argon atmosphere to obtain a silicon carbide sintered body. The sintered body was polished and subjected to in-situ friction and wear tests in 10 MPa seawater conditions to simulate a 1000-meter sea depth environment. The wear volume was tested using white light interferometry to calculate the wear rate.

[0075] Comparative Example 4

[0076] Weigh 85.81g of silicon carbide powder with an average particle size of 1 micron and an oxygen content of 0.5wt%, 1.18g of silicon oxide powder with an average particle size of 0.5 micron, and 13.02g of ytterbium oxide powder with an average particle size of 1 micron and place them in a ball mill. At this time, it can be calculated that the silicon carbide powder raw material contains about 0.81g of silicon dioxide, the total amount of silicon dioxide is 1.99g, the molar ratio of ytterbium oxide to silicon oxide is about 1:1, and the total amount of ytterbium oxide and silicon oxide accounts for 15wt% of the total amount of raw materials. Add 100g of silicon carbide balls and 60g of ethanol to planetary ball mill for 4 hours, dry the slurry after ball milling in a blast drying oven at 50℃ for 3 hours, and obtain the sample after sieving. The powder was dry pressed at 40 MPa, cold isostatically pressed at 150 MPa, and pressurelessly sintered at 1900°C for 2 hours in an argon atmosphere to obtain a silicon carbide sintered body. The sintered body was polished and subjected to in-situ friction and wear tests in 10 MPa seawater conditions to simulate a 1000-meter sea depth environment. The wear volume was tested using white light interferometry to calculate the wear rate.

[0077] Test Case

[0078] The properties of the silicon carbide sintered bodies prepared in Examples 1 to 12 and Comparative Examples 1 to 4 were tested. The wear rates of the silicon carbide sintered bodies prepared in Examples 1 to 12 and Comparative Examples 1 to 4 under deep sea conditions are shown in Table 1. The tests found that the wear rates of all samples in Examples 1 to 12 under deep sea conditions were all less than 6×10 -9 / mm 3 N -1 m -1 By comparing with Comparative Examples 1 and 2, it is found that when the silicon oxide content is too high or too low, the ratio of rare earth oxide to silicon oxide is too low or too high, which leads to a serious decrease in the wear resistance of silicon carbide ceramics under deep-sea conditions. By comparing with Comparative Example 3, it is found that too low a sintering aid content will lead to a decrease in the degree of densification, and then a serious decrease in wear resistance. By comparing with Comparative Example 4, it is found that too high a sintering aid content will also affect the wear resistance of the sintered body, which may be due to the decrease in the content of silicon carbide crystalline phase and the decrease in mechanical wear resistance.

[0079] Table 1 Wear rates of silicon carbide ceramics prepared in different embodiments and comparative examples in deep sea environment

[0080]

[0081]

[0082] From the above embodiments, it can be seen that the present invention proposes a wear-resistant silicon carbide sintered body under deep-sea conditions. By forming a water-corrosion-resistant rare earth silicate grain boundary phase network at the grain boundary of the silicon carbide sintered body, the main components of the grain boundary phase are one or more of Yb2SiO5, Yb2Si2O7, Lu2SiO5, and Lu2Si2O7. During the wear process, the silicon carbide grains in the silicon carbide sintered body can inhibit the progress of mechanical wear, and the presence of the grain boundary phase plays a role in reducing water corrosion and wear, and ultimately greatly improves the wear resistance of silicon carbide ceramics in seawater environments. The rare earth silicate grain boundary phase in the silicon carbide sintered body provided by the present invention is mainly Yb2SiO5, Yb2Si2O7, Lu2SiO5, and Lu2Si2O7, and the grain boundary phase content is 6-12wt% of the silicon carbide sintered body, and the total amount of Yb2SiO5, Yb2Si2O7, Lu2SiO5, and Lu2Si2O7 accounts for more than 70wt% of the grain boundary phase.

[0083] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A silicon carbide sintered body, characterized in that: The silicon carbide sintered body comprises a silicon carbide crystalline phase and a grain boundary phase, wherein the grain boundary phase comprises a rare earth silicate grain boundary phase; and the rare earth silicate grain boundary phase comprises one or more of Yb2SiO5, Yb2Si2O7, Lu2SiO5 and Lu2Si2O7.

2. The silicon carbide sintered body according to claim 1, characterized in that The total content of the Yb2SiO5, Yb2Si2O7, Lu2SiO5 and Lu2Si2O7 phases accounts for more than 70wt% of the total amount of the grain boundary phase.

3. The silicon carbide sintered body according to claim 1 or 2, characterized in that: The content of the silicon carbide crystal phase accounts for 88-94 wt % of the silicon carbide sintered body, and the content of the grain boundary phase accounts for 6-12 wt % of the silicon carbide sintered body.

4. The method for preparing a silicon carbide sintered body according to any one of claims 1 to 3, characterized in that: The following steps are involved: Silicon carbide powder and sintering aid powder are mixed to obtain a mixed powder, wherein the sintering aid includes at least one of rare earth oxides, rare earth silicates and silicon oxide, and the ratio of the total molar amount of the rare earth oxide converted in the mixed powder to the total molar amount of silicon dioxide converted in the mixed powder is 1: 0.8~1.3 or 1:1.8~2.1; The mixed powder is sintered to obtain the silicon carbide sintered body.

5. The preparation method according to claim 4, characterized in that: The total mass of the rare earth oxide and silicon dioxide in the mixed powder accounts for 6-12 wt % of the mass of the mixed powder.

6. The preparation method according to claim 4, characterized in that: The particle sizes of the silicon carbide powder and the sintering aid powder are independently 0.05 to 200 microns.

7. The preparation method according to claim 4 or 6, characterized in that: The mixing comprises the following steps: Silicon carbide powder, sintering aid powder, grinding balls and solvent are mixed and ground to obtain slurry, wherein the grinding includes one or more of planetary ball milling, drum ball milling and sand milling, the solvent includes ethanol and / or water, and the grinding time is 2 to 24 hours; The slurry is dried and sieved in sequence to obtain the mixed powder.

8. The preparation method according to claim 4, characterized in that: The sintering includes pressureless sintering, hot pressing sintering or spark plasma sintering after dry pressing; The sintering temperature is 1700-2100° C., and the heat preservation time is 5-120 minutes.

9. Use of the silicon carbide sintered body according to any one of claims 1 to 3 or the silicon carbide sintered body prepared by the preparation method according to any one of claims 4 to 8 in sealing materials.

10. The use according to claim 9, characterized in that: The sealing material is a dynamic sealing material used in deep sea conditions, and the seawater depth in the deep sea conditions is ≥1000 meters.